Retrospective analysis and forecasting of the spread of viruses in real time: the case of COVID-19 in St. Petersburg and Moscow in 2020–2021 - Victor V. Zakharov; Yulia E. Balykina (Вопросы вирусологии)
The aim of the study is to apply mathematical methods to generate forecasts of the dynamics of random values of the percentage increase in the total number of infected people and the percentage increase in the total number of recovered and deceased patients. The obtained forecasts are used for retrospective forecasting of COVID-19 epidemic process dynamics in St. Petersburg and in Moscow.